The immune system response to the SARS-CoV-2 virus: an update - Klenerman, Paul (Henry Stewart Talks, 2020)
Updated knowledge on the immune response to SARS-COV-2, Antibody tests and their future role, Current knowledge on how the lungs are being affected during infection, A hypothesis on why age ranges respond differently to infection, Animal models to study SARS-COV-2 infection